Pengembangan Angkutan Umum Terintegrasi di Kota Surakarta - Anandhika Arifianto (Department of Urban and Regional Planning, Faculty of Engineering, Diponegoro University, 2019)
Development of public transportation in the main steps to unravel traffic congestion in Surakarta City. Various alternative public transports are provided which are directly integrated, such as Batik Solo Trans (BST), city transportation, Werkudara-level buses, and railbus. Directly proportional to the number of public transportation equipment will have a major impact on the breakdown of traffic congestion that has occurred. There have been many people in Surakarta City who utilize integrated and sustainable public public transportation.